Overexpression of AHL9 accelerates leaf senescence in Arabidopsis thaliana - Yusen Zhou (BMC Plant Biology, 2022)
Abstract Background Leaf senescence, the final stage of leaf growth and development, is regulated by numerous internal factors and environmental cues. Ethylene is one of the key senescence related hormones, but the underlying molecular mechanism of ethylene-induced leaf senescence remains poorly understood. Results In this study, we identified one AT-hook like (AHL) protein, AHL9, as a positive regulator of leaf senescence in Arabidopsis thaliana. Overexpression of AHL9 significantly accelerates age-related leaf senescence and promotes dark-induced leaf chlorosis. The early senescence phenotype observed in AHL9 overexpressing lines is inhibited by the ethylene biosynthesis inhibitor aminooxyacetic acid suggesting the involvement of ethylene in the AHL9-associated senescence. RNA-seq and quantitative reverse transcription PCR (qRT-PCR) data identified numerous senescence-associated genes differentially expressed in leaves of AHL9 overexpressing transgenic plants. Conclusions Our investigation demonstrates that AHL9 functions in accelerating the leaf senescence process via ethylene synthesis or signalling.